Adoption of innovations in harvesting methods of the grape: A case study in Charikar and Bagram districts of Parwan province, Afghanistan - Dadkhwah, Zafaruddin; Demiryürek, Kürşat (International Journal of Scientific Research and Management (IJSRM), 2020)
The main objectives of this study were to determine the extent of innovation in the grape harvest, and the rate of familiarity and usability of innovations by farmers in Parwan province. The data were collected as primary data, included face to face interviews with 120 grape growers and local authorities in 20 villages spread across the two districts of Charikar and Bagram provinces of Parwan, Afghanistan. The data was analyzed by (SPSS 22) Package. According to the results, the size of agricultural land, land allocated to grape production have the most similarities; however, the findings show that grape yield was impressed by the application of farmers' innovations and knowledge by the user of innovation in the harvest stage grape production. The membership of farmers in agricultural organizations is very weak, and only 8.2% of the farmers have membership in the organization. And also, the advantages and disadvantages of using innovations were evaluated. The advatages were evaluated by six options (Saving Time, Increasing demand for the product, Wastes Reduction in the product, Better management,  Easy harvest, Employment of less laborer), and all of them given high importance (HI). The disadvantages were evaluated in four options, of which only the the item ''Not economic'' was given (HI) while the remaining three disadvantages were in (LI) category. Familiarity and usability of innovations have different results; most of the farmers are familiar with innovations. However, the application of innovations is less than it is familiarity